Glycyrrhizic acid protects against temporal lobe epilepsy in young rats by regulating neuronal ferroptosis through the miR‐194‐5p/PTGS2 axis - Ting‐Ting Yi; Li‐Mei Zhang; Xiang‐Nan Huang (Kaohsiung Journal of Medical Sciences, 2023)
Abstract Temporal lobe epilepsy (TLE) leads to extensive degradation of the quality of life of patients. Glycyrrhizic acid (GA) has been reported to exert neuroprotective effects on status epilepticus. Herein, the current study set out to explore the functional mechanism of GA in TLE young rats. Firstly, TLE young rat models were established using the lithium chloride and pilocarpine regimen and then subjected to treatment with different doses of GA, miR‐194‐5p‐antagomir, or/and sh‐prostaglandin‐endoperoxide synthase 2 (PTGS2) to observe changes in iron content, glutathione and malondialdehyde levels, and GPX4 (glutathione peroxidase 4) and PTGS2 protein levels in the hippocampus. Neuronal injury and apoptosis were assessed through HE, Nissl, and TUNEL staining. Additionally, the expression patterns of miR‐194‐5p were detected. The binding site of miR‐194‐5p and PTGS2 was verified with a dual‐luciferase assay. Briefly, different doses of GA (20, 40, and 60 mg/kg) reduced the epileptic score, frequency, and duration in TLE young rats, along with reductions in iron content, lipid peroxidation, neuronal injury, and apoptosis in the hippocampus. Silencing of miR‐194‐5p partly annulled the action of GA on inhibiting ferroptosis and attenuating neuronal injury in TLE young rats. Additionally, PTGS2 was validated as a target of miR‐194‐5p. GA inhibited ferroptosis and ameliorated neuronal injury in TLE young rats via the miR‐194‐5p/PTGS2 axis. Overall, our findings indicated that GA exerts protective effects on TLE young rats against neuronal injury by inhibiting ferroptosis through the miR‐194‐5p/PTGS2 axis.